2022
DOI: 10.3390/antibiotics11091157
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of an Artificial ATP Deficit Triggers Antibiotic Production in Streptomyces lividans

Abstract: In most Streptomyces species, antibiotic production is triggered in a condition of phosphate limitation, a condition that is known to be correlated with a low intracellular ATP content compared to growth in a condition of phosphate proficiency. This observation suggests that a low ATP content might be a direct trigger of antibiotic biosynthesis. In order to test this hypothesis, we introduced into the model strain Streptomyces lividans, a functional and a non-functional ATPase cloned into the replicative vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…A reduced generation of ATP due to nutritional limitation in condition of high cell density or DX-mediated ATP degradation were correlated with the triggering of the production of specific antibiotics. This is consistent with previous work that demonstrated that the over-expression of an ATPase triggers antibiotic production in the weak producer Streptomyces lividans ( Seghezzi et al, 2022 ). However, even at high plating density, A37 produces higher amounts of the same specialized metabolites than A36 ( Supplementary Table S2 ).…”
Section: Resultssupporting
confidence: 93%
“…A reduced generation of ATP due to nutritional limitation in condition of high cell density or DX-mediated ATP degradation were correlated with the triggering of the production of specific antibiotics. This is consistent with previous work that demonstrated that the over-expression of an ATPase triggers antibiotic production in the weak producer Streptomyces lividans ( Seghezzi et al, 2022 ). However, even at high plating density, A37 produces higher amounts of the same specialized metabolites than A36 ( Supplementary Table S2 ).…”
Section: Resultssupporting
confidence: 93%
“…Consequently, a weaker oxidative stress could explain the lower ACT production of the TD variant compared to the original strain. Nonetheless, the TD variant still produces ACT at a low level in the condition of Pi limitation ( Figure 1 A), a condition known to promote the activation of the oxidative metabolism and thus the generation of oxidative stress [ 44 , 45 ], whereas ACT production is undetectable in the condition of Pi proficiency ( Figure 1 B). The remaining low level of ACT production in the TD variant could be due to a low level of oxidative stress due the very active fatty acids/lipids biosynthesis taking place in the TD variant.…”
Section: Discussionmentioning
confidence: 99%
“…7−10 Phosphate limitation or a low intracellular ATP content causes a stress response that triggers specialized metabolite production in Streptomyces. 11,12 Carbonyl cyanide 3-chlorophenylhydrazone (CCCP) is an oxidative phosphorylation inhibitor that inhibits the synthesis of ATP, and it has been used to induce actinorhodin production in respiratory mutants of Streptomyces coelicolor A3(2). 13 NPs assembled by type I modular polyketide synthases (PKSs) have attracted great attention due to their broad spectrum of biological activities 14 and complex biosynthetic mechanisms.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, many of these BGCs are poorly expressed in laboratory growth conditions, making identification of the NPs they encode challenging . Activation of such “silent” BGCs enables the discovery of NPs with unprecedented structures and intriguing bioactivities. Phosphate limitation or a low intracellular ATP content causes a stress response that triggers specialized metabolite production in Streptomyces. , Carbonyl cyanide 3-chlorophenylhydrazone (CCCP) is an oxidative phosphorylation inhibitor that inhibits the synthesis of ATP, and it has been used to induce actinorhodin production in respiratory mutants of Streptomyces coelicolor A3(2) …”
Section: Introductionmentioning
confidence: 99%